The Study on the Diagnosis of Endometritis in the Infertile Cows by Clinical Examination and Biopsy - Apaydın, Ali Mükremin; Özer, Harun; Kalkan, Cahit; Öcal, Halis; Bostancıoğlu, Hatice; Eröksüz, Yesari (Van Yüzüncü Yıl Üniversitesi, 1991)
In this study, the uteri from 190 infertile, 10 healty and 30slaughtered cows were used as material. The infertile cows were clinically examined,and biopsy was carried out in the uterus. The uterine samples obtained fromslaughtered Cows  at estrus, metaestrus and diestrus stages were used as control. Theuteri of the healty 10 cows were biopsied at the same stages.Histopathological examinations were conducted in all samples.In the result of the examinations, 170 of 190 infertile cows (89,5 %) werefound with endometritis. One hundered and twenty eight, 28 and 17 of theese cowswere found to be I,II and III grades endometritis, respectivaly.Forty five cows which were clinically endometritis were also histopathologicallyendometritis.One hundred twenty eight of 145 repeat breeder cows were found histopathologically endometritis (86,2%).

Çalışmada, 190 infertile inek, 10 sağlıklı inek ve kesimden sonra alınan30 sağlıklı inek uterusu materyal olarak kullanıldi. İnfertil ineklerin klinikmuayeneneleri yapıldıktan sonra uterus biyopsisi yapıldL Mezbahadan östrus, meta-östrus ve diöstrüste onar adet olmak üzere toplam 30 uterus kesiti yapıldi. Sağlıklı 10 inekten de aynı devrelerde biyopsi numunesi alindi. Biyopsi numuneleri ve mezbaha materyalinden alınan kesitlerde histopatolojikmuayeneler yapıldi.Yapılan muayenelerde, 190 infertil inekten 170'inde endometritis bulundu.Bunlardan 128 'i I.derece, 28 II. derece, 17'si de III. derece endometritisli, klinik belirti ·bulunan 45 inek, histopatolojik olarak da endometritisli, Hiç bir klinik bozuklukbulunmadığı halde döl tutmayan 145 inekten 128'i histopatolojik olarak endometritislibulundu (%86,2).
İNFERTİL İNEKLERDE ENDOMETRİTİSİN KLİNİK MUAYENE VE BİYOPSİ İLE TEŞHİSİ ÜZERİNE ÇALIŞMA